Strategi Manajemen Kepemimpinan dalam Meningkatkan Kualitas Kinerja Guru - Shofiyah, Elik (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to analyze how leadership management strategies can improve teacher performance in schools. Effective leadership management involves not only planning and implementation, but also continuous evaluation and follow-up. Using qualitative research methods through observation, interviews, and documentation, this study was conducted in several schools in region X. The results of the study indicate that structured leadership management supported by training and regular evaluation has a significant impact on improving teacher performance. Teachers who are involved in teaching planning and evaluation are able to manage classes better, apply innovative teaching methods, and improve student learning outcomes. In conclusion, effective leadership management is an important factor in supporting teacher performance and improving the overall quality of education.